The Concept of Al-Ta’ah (Obedience) To Muslim Leadership From The Islamic Political Thought - Ali, Wan Zailan Kamaruddin Wan; Ismail, Ahmad Zuhdi; Shahruddin, Mohd Solahuddin; Gatara, Asep Sahid (Politicon : Jurnal Ilmu Politik, 2021)
This article, as the title suggests, is to examine the ideas and concepts of obedience to Muslim leadership from Islamic Political Thought. Using qualitative methods and content analysis techniques, this article raises other issues involved such as the discussion of obedience to ideals and reality. it is certain that Islam has asserted that those who are entitled to be obeyed are Allah SWT, Prophet Muhammad SAW and the best and pious Muslim leaders (uli al-amr, Imam, Khalifah, Wali, Wasi, ’Alim). and Amir) at any time. Islam also states that following such a leader means following the truth.